2022
DOI: 10.1186/s13020-022-00620-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial spore genetic marker technology, a potential technology for traditional Chinese medicine traceability system

Abstract: Traditional Chinese medicine (TCM) has a long history, rich clinical experience, and unique advantages in the prevention and treatment of diseases. The quality and safety of Chinese medicinal materials (CMMs) directly affect the clinical efficacy and development of the TCM industry. However, confused provenance, counterfeiting and adulteration of CMMs hinder the acceptance of its therapeutic benefits in modern society. Therefore, the establishment and improvement of a TCM traceability system would be conducive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…To address the possible risks of releasing genetically modified organisms into the environment, Qian et al [17] built clever safeguards into the BMS system to prevent the accidental spread and proliferation of the microbial labels. Additionally, Zhao et al [47] demonstrated the use of BMS for fast, easy, and accurate food traceability and its great potential for standardization in the Chinese materia medica market. Silica is an ideal material for encapsulation due to its non-toxicity, high inertia and exceptional barrier characteristics.…”
Section: Generation and Validation Of Silica Particles With Encapsula...mentioning
confidence: 99%
“…To address the possible risks of releasing genetically modified organisms into the environment, Qian et al [17] built clever safeguards into the BMS system to prevent the accidental spread and proliferation of the microbial labels. Additionally, Zhao et al [47] demonstrated the use of BMS for fast, easy, and accurate food traceability and its great potential for standardization in the Chinese materia medica market. Silica is an ideal material for encapsulation due to its non-toxicity, high inertia and exceptional barrier characteristics.…”
Section: Generation and Validation Of Silica Particles With Encapsula...mentioning
confidence: 99%
“…DNA-barcoding technology has made great progress in the molecular identification of Chinese herbs, and has been included in the Pharmacopoeia of the People’s Republic of China. However, after concoction or other processing operations, the DNA of Chinese herbal medicines can be degraded, thus affecting identification [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only with stable-quality, Chinese herbs can ensure the maximum clinical efcacy of TCM. However, the multilinking and complex performances on the supply chain of Chinese herbs, coupled with the low level of information technology, cause the source and processing of Chinese herbs to be opaque [1]. Even more, some of the links on the supply chain of Chinese herbs are out of control, which results in the mixing of herbs, commercial adulteration, and underspecifed harvesting and processing.…”
Section: Introductionmentioning
confidence: 99%